(untitled) (International Journal of Engineering and Computer Science, 2017)
Image processing is part of signal processing. One of the typical operations perform on image processing is image segmentation. Segmentation refers to the process of partitioning a digital image into multiple segments (sets of pixels, also known as super pixels).Image segmentation is typically used to locate objects and boundaries (lines, curves, etc.) in images. More precisely, image segmentation is the process of assigning a label to every pixel in an image such that pixels with the same label share certain visual characteristics. The result of image segmentation is a Set of segments that collectively cover the entire image, or a set of contours extracted from the image. each of the pixels in a region are similar with respect to some characteristic or computed property, such as colour, intensity, or texture. Due to the importance of image segmentation a number of algorithms have been Proposed but based on the image that is inputted the algorithm should be chosen to get the best results. In this paper the author gives a study of the various algorithms that are available for colour images, text and gray scale images. In this paper, I have presented various image segmentation approaches like pixel based segmentation, edge base segmentation, fixation based segmentation etc. and there are various applications if image segmentation out of which finger code generation using SPFB (singular point feature block) is explain in detail .paper p